Angiotensin II receptor blockers are safe in patients with prior angioedema related to angiotensin‐converting enzyme inhibitors – a nationwide registry‐based cohort study. (8th January 2019) - Rasmussen, Eva Rye; Pottegård, Anton; Bygum, Anette; von Buchwald, Christian; Homøe, Preben; Hallas, Jesper
Abstract: Background: It has long been suggested that angiotensin‐converting enzyme inhibitors (ACEi) and angiotensin II receptor blockers (AT2s) have some degree of 'cross‐reactivity' in causing angioedema. Therefore, caution has been advised when switching patients with ACEi‐related angioedema to an AT2. Objectives: To clarify whether AT2s can be used safely in patients with a history of angioedema during ACEi treatment and to estimate the incidence rate of angioedema in patients subsequently treated with other antihypertensive drugs (beta‐adrenergic blockers, calcium channel blockers, thiazides and analogues) or no antihypertensives. Methods: This is a nationwide retrospective registry‐based cohort study of the Danish population during the period 1994 to 2016, and it uses Danish health registries. Propensity score adjusted and conventional proportional hazards regression models have been employed. Results: A total of 1 106 024 ACEi users were identified. In total, 5 507 (0.5%) of these patients had experienced angioedema during ACEi treatment and were included in the study. The highest risk of angioedema recurrence was associated with continued ACEi use at an adjusted hazard ratio of 1.45 (95% CI, 1.19 to 1.78). An inverse association was found between AT2s and angioedema (adjusted hazard ratio, 0.39; 95% CI, 0.30 to 0.51) compared with other antihypertensives (adjusted hazard ratios, 0.77 to 0.97). Conclusions: Compared with other antihypertensive drugs, AT2s do not increase the incidence of angioedema in patients with previous ACEi‐related angioedema. Abstract : Click here to view the Editorial Comment by N. Javaud et al .